Analysis of Security Criteria for IoT-Based Supply Chain: A Case Study of FMCG Industries - Nozari Hamed; Fallah Mohammad; Szmelter-Jarosz Agnieszka; Krzemiński Maciej (Central European Management Journal, 2021)
Purpose: In supply chains, creating a secure space for data production, sending, storing, and analysis has always been a critical issue. The main goal of this research was to evaluate the importance of various security criteria in an intelligent supply chain system.